CoWO4/Reduced Graphene Oxide Nanocomposite-Modified Screen-Printed Carbon Electrode for Enhanced Voltammetric Determination of 2,4-Dichlorophenol in Water Samples - Somayeh Tajik; Hadi Beitollahi; Fariba Garkani Nejad; Reza Zaimbashi (Micromachines)
Water pollution with phenolic compounds is a serious environmental issue that can pose a major threat to the water sources. This pollution can come from various agricultural and industrial activities. Phenolic compounds can have detrimental effects on both human health and the environment. Therefore, it is essential to develop and improve analytical methods for determination of these compounds in the water samples. In this work, the aim was to design and develop an electrochemical sensing platform for the determination of 2,4-dichlorophenol (2,4-DCP) in water samples. In this regard, a nanocomposite consisting of CoWO4 nanoparticles (NPs) anchored on reduced graphene oxide nanosheets (rGO NSs) was prepared through a facile hydrothermal method. The formation of the CoWO4/rGO nanocomposite was confirmed via different characterization techniques. Then, the prepared CoWO4/rGO nanocomposite was used to modify the surface of a screen-printed carbon electrode (SPCE) for enhanced determination of 2,4-DCP. The good electrochemical response of the modified SPCE towards the oxidation of 2,4-DCP was observed by using cyclic voltammetry (CV) due to the good properties of CoWO4 NPs and rGO NSs along with their synergistic effects. Under optimized conditions, the CoWO4/rGO/SPCE sensor demonstrated a broad linear detection range (0.001 to 100.0 µM) and low limit of detection (LOD) (0.0007 µM) for 2,4-DCP determination. Also, the sensitivity of CoWO4/rGO/SPCE for detecting 2,4-DCP was 0.3315 µA/µM. In addition, the good recoveries for determining spiked 2,4-DCP in the water samples at the surface of CoWO4/rGO/SPCE showed its potential for determination of this compound in real samples.